Mycophenolate mofetil as an alternative treatment in sarcoidosis. (October 2019) - Papiris, Spyros; Stagaki, Eleni; Papadaki, Georgia; Kolilekas, Lykourgos; Korbila, Ioanna; Apollonatou, Vassiliki; Kallieri, Maria; Gialafos, Helias; Chatziioannou, Sofia; Papaioannou, Adriana I.; Manali, Effrosyni D.
Abstract: Introduction: In sarcoidosis although no better drug therapy than corticosteroids (CS) has emerged, alternative immunosuppressive agents are used when indicated. Mycophenolate mofetil (MMF) presents rapid action, a considerable safety profile and absence of lung toxicity. Few data exist so far on its use in patients with sarcoidosis. This is a retrospective study on the effectiveness and safety of MMF in patients with sarcoidosis. Materials and methods: All patients with biopsy proven sarcoidosis treated for at least 1 year with MMF from 2008 to 2017 in our department are evaluated. Results: Eight patients with both pulmonary and extrapulmonary disease are included in the analysis. During follow-up, symptoms and chest radiological findings improved in all. A statistically significant improvement of FEV1 and FVC is reported (p = 0.010 and p = 0.021 respectively). Cardiac and renal disease resolved during treatment while dermal disease significantly improved. MMF permitted CS dose reduction from 15.0 (10.0, 35.0) to 2.5 (0.0, 5.0) mg prednisolone (or equivalent), p = 0.016. All patients but one, tolerated well MMF. Conclusion: MMF as an alternative drug in systemic sarcoidosis, proved safe and effective, permitting the reduction of the dose of oral CS and leading to clinical, functional and radiological improvement.